Pengaruh Konsentrasi Larutan Daun Cengkeh Terhadap Jumlah Lalat Hijau Yang Hinggap Selama Proses Penjemuran Ikan Asin - Khonsa Abdullah S.; Dindin Wahyudin (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2015)
Abstract: The effect of concentration solution leaf clovers (syzigium aromaticum) to total flies green (chrysomya megacephala) which perch in fish salted during drying process. The Food is anything that comes from biological sources and water, whether treated or untreated, which is applied as a food or beverage for human consumption. Almost 65% of fishery products in Indonesia is still processed by salting which produces salted fish products. The leaf clovers (Syzigium aromaticum) is one kind of plant that can be used as a natural insecticide reppelent vegetable because it contains an active substance that is believed Euganol not liked by the flies. The purpose of this research conducted to determine differences in various concentration of leaf clovers (Syzigium aromaticum) on the number of green flies (Chrysomya megacephala) that settle during the drying process of salted fish. Type of research was experimental design with posttest only control group design. The results of this study include the average number of flies alighted during the drying process anchovies (8 hours), using a concentration of 1.56% leaf clovers as many as eight tails, 3.12% concentration of 7 animals. 6.25% concentration of 4 tails, a concentration of 12.5% as much as 3 tails, a concentration of 25% by 2 tails, and a concentration of 50% as much as 1 tail. With a P value (0.000) <α confidence level of 95%, or by comparing the value of F (1363.000)> F table (4.06), then there is the influence of leaf clovers various concentration on the number of flies that settle during the drying process anchovies. The application of this method can be applied especially in an environment that produces the manufacture of salted fish. as a replacement for chemical insecticides to repel flies. Keywords: Reppelent; Syzigium aromaticum; Chrysomya megacephala